A Rapid Systematic Review of Public Responses to Health Messages Encouraging Vaccination against Infectious Diseases in a Pandemic or Epidemic - Lawes-Wickwar, Sadie; Ghio, Daniela; Tang, Mei Yee; Keyworth, Chris; Stanescu, Sabina; Westbrook, Juliette; Jenkinson, Elizabeth; Kassianos, Angelos P.; Scanlan, Daniel; Garnett, Natalie; Laidlaw, Lynn; Howlett, Neil; et al. (Vaccines (Basel), 2021)
Public health teams need to understand how the public responds to vaccination messages in a pandemic or epidemic to inform successful campaigns encouraging the uptake of new vaccines as they become available. A rapid systematic review was performed by searching PsycINFO, MEDLINE, healthevidence.org, OSF Preprints and PsyArXiv Preprints in May 2020 for studies including at least one health message promoting vaccine uptake of airborne-, droplet- and fomite-spread viruses. Included studies were assessed for quality using the Mixed Methods Appraisal Tool (MMAT) or the Assessment of Multiple Systematic Reviews (AMSTAR), and for patient and public involvement (PPI) in the research. Thirty-five articles were included. Most reported messages for seasonal influenza (n = 11; 31%) or H1N1 (n = 11; 31%). Evidence from moderate to high quality studies for improving vaccine uptake included providing information about virus risks and vaccination safety, as well as addressing vaccine misunderstandings, offering vaccination reminders, including vaccination clinic details, and delivering mixed media campaigns across hospitals or communities. Behavioural influences (beliefs and intentions) were improved when: shorter, risk-reducing or relative risk framing messages were used; the benefits of vaccination to society were emphasised; and beliefs about capability and concerns among target populations (e.g., vaccine safety) were addressed. Clear, credible, messages in a language target groups can understand were associated with higher acceptability. Two studies (6%) described PPI in the research process. Future campaigns should consider the beliefs and information needs of target populations in their design, including ensuring that vaccine eligibility and availability is clear, and messages are accessible. More high quality research is needed to demonstrate the effects of messaging interventions on actual vaccine uptake.